2018
DOI: 10.1021/acs.inorgchem.7b03100
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hydration/Dehydration-Induced Vapochromic Behavior of a Charge-Transfer Salt Comprising Viologen and Hexacyanidoferrate(II)

Abstract: We successfully prepared and crystallographically characterized the first intermolecular charge-transfer (CT)-based vapochromic compound, (EV)(HO)[Fe(CN)] (1-Wet, EV: 1,1'-diethyl-4,4'-bipyridine-1,1'-diium), an ethyl viologen-containing CT salt. 1-Wet, which is purple in color, is transformed into a brown powder (1-Dry) upon exposure to methanol vapor, drying over silica gel, or heating; 1-Dry returns to 1-Wet upon exposure to water vapor. These color changes are induced by hydration and dehydration, and grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Due to the addition of the HCl solution, the lattice water molecule, and the terminal cyano group of the [Fe(CN) 6 ] 3− entity along the c axis were both protonated by a half-occupied hydrogen atom. Similar hydronium ions as counter cations has recently been found in a charge-transfer (CT) salt of hexacyanidoferrate(II) [44]. And the hydrogen isocyanide (HNC) system has been discovered in the crystal lattice of similar "cyanometallic acids" [45].…”
Section: Crystal Structure Of Compounds 1-3mentioning
confidence: 74%
“…Due to the addition of the HCl solution, the lattice water molecule, and the terminal cyano group of the [Fe(CN) 6 ] 3− entity along the c axis were both protonated by a half-occupied hydrogen atom. Similar hydronium ions as counter cations has recently been found in a charge-transfer (CT) salt of hexacyanidoferrate(II) [44]. And the hydrogen isocyanide (HNC) system has been discovered in the crystal lattice of similar "cyanometallic acids" [45].…”
Section: Crystal Structure Of Compounds 1-3mentioning
confidence: 74%
“…To our best knowledge, 1 and 2 represent the very first example of [M–CN–M′] coordination complexes featuring [Fe­(CN) 6– x (CNH) x ] n − as a building block, although the protonation of hexacyanometallates have been studied spectroscopically and crystallographically in few cases . Note that this type of molecular architecture was obtained only with m -halogenated anilinium derivatives as cations.…”
Section: Resultsmentioning
confidence: 99%
“…The solvatochromism of such a CTC has not been given much attention but constitutes an interesting chromic effect of the response of the complex to its environment. Acknowledging the chromic behavior of this class of CTCs, Tanaka et al recently reported on the reversible vapochromic and environment-sensitive character of crystalline CTCs between ethyl-viologen and hexacyanoferrate(II) anions [91]. The color of a dry sample of CTC 53b (see Table 2) was found to be significantly different from that of a wet sample (see Figure 24a).…”
Section: Charge Transfer Complexes Of Viologensmentioning
confidence: 98%